Seed traits matter—Endozoochoric dispersal through a pervasive mobile linker. Issue 24 (14th December 2021) - Stiegler, Jonas; Kiemel, Katrin; Eccard, Jana; Fischer, Christina; Hering, Robert; Ortmann, Sylvia; Strigl, Lea; Tiedemann, Ralph; Ullmann, Wiebke; Blaum, Niels
Abstract: Although many plants are dispersed by wind and seeds can travel long distances across unsuitable matrix areas, a large proportion relies on co‐evolved zoochorous seed dispersal to connect populations in isolated habitat islands. Particularly in agricultural landscapes, where remaining habitat patches are often very small and highly isolated, mobile linkers as zoochorous seed dispersers are critical for the population dynamics of numerous plant species. However, knowledge about the quali‐ or quantification of such mobile link processes, especially in agricultural landscapes, is still limited. In a controlled feeding experiment, we recorded the seed intake and germination success after complete digestion by the European brown hare ( Lepus europaeus) and explored its mobile link potential as an endozoochoric seed disperser. Utilizing a suite of common, rare, and potentially invasive plant species, we disentangled the effects of seed morphological traits on germination success while controlling for phylogenetic relatedness. Further, we measured the landscape connectivity via hares in two contrasting agricultural landscapes (simple: few natural and semi‐natural structures, large fields; complex: high amount of natural and semi‐natural structures, small fields) using GPS‐based movement data. With 34, 710 seeds of 44 plant species fed, one of 200 seeds (0.51%) with seedlings of 33 species germinated from feces. Germination after complete digestion was positively related to denser seeds with comparatively small surface area and a relatively slender and elongated shape, suggesting that, for hares, the most critical seed characteristics for successful endozoochorous seed dispersal minimize exposure of the seed to the stomach and the associated digestive system. Furthermore, we could show that a hare's retention time is long enough to interconnect different habitats, especially grasslands and fields. Thus, besides other seed dispersal mechanisms, this most likely allows hares to act as effective mobile linkers contributing to ecosystem stability in times of agricultural intensification, not only in complex but also in simple landscapes. Abstract : The most critical seed characteristics for successful endozoochorous seed dispersal by hares minimize exposure of the seed to the digestive system (i.e., dense seeds with a small surface area and an elongated shape). In addition, a hare's retention time is long enough to interconnect different habitats, especially grasslands and crop fields. Thus, besides other seed dispersal mechanisms, this most likely allows hares to act as effective mobile linkers contributing to ecosystem stability during times of agricultural intensification.